Pengaruh Information Technology Relatedness terhadap Kinerja Perusahaan (Penelitian terhadap Perusahaan Perbankkan di Jateng) - Luluk Muhimatul Ifada (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine the influence of information technology (IT) relatedness on corporate performance. IT relatedness is measured using a reflective second-order factor modeling approach to capture complementarities among the four dimensions of IT relatedness (IT strategy making processes, IT vendor management processes, IT human resource management processes and IT infrastructure). Based on the resource-based view of diversification and the economic theory of complementarities, the two major sources of cross-unit IT synergy in the corporate are the relatedness and complementarities of IT resources.  According RBV concept, the use of IT relatedness as a complementarities unit create super-additive value synergies and can be used as competitive sustainability advantage to improve corporate performance Collecting data by a survey of 93 office managers branch banking in Central Java, the study finds that the information technology relatedness has a positive influence on corporate performance as hypothesized suggesting that the super-additive value synergies arising from the use of a complementary set of IT resources and management processes have significant effects on corporate performance.